Arabic Language Learning Problems and Solutions at Abu Bakar Ash-Syiddiq Integrated Islamic Junior High School - Wahyudi, Hakmi; Siregar, Juwairiyah; Priambodo, Thrio (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Learning Arabic is learning a foreign language, which will cause difficulties for students to learn it because it is not their mother tongue so problems will arise, both linguistic and non-linguistic. This research aims to describe the problems of learning Arabic and the solutions teachers implement to overcome these problems. The research method used is qualitative. The data collection technique is interviews. The results of this research state that linguistic problems in learning Arabic are found in the sound system and microdata. The non-linguistic problems include inadequate learning facilities and insufficient learning time. The solution to this problem is the repetition method so that students can pronounce the sound system correctly, giving five vocabulary words at each meeting, utilizing existing media, applying exciting methods, and implementing Arabic Day. A teacher must try to improve his competence to solve learning problems.ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù‡Ùˆ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© Ù…Ù† Ø´Ø£Ù†Ù‡ Ø£Ù† ÙŠØ³Ø¨Ø¨ ØµØ¹ÙˆØ¨Ø§Øª Ù„Ù„Ø·Ù„Ø§Ø¨ Ù„ØªØ¹Ù„Ù…Ù‡Ø§ Ù„Ø£Ù†Ù‡Ø§ Ù„ÙŠØ³Øª Ù„ØºØ© Ø§Ù„Ø£Ù…ØŒ Ù„Ø°Ù„Ùƒ Ø³ØªÙƒÙˆÙ† Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© ÙˆØ§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ØºÙŠØ± Ø§Ù„Ù„ØºÙˆÙŠØ© Ø¹Ø¯ÙŠØ¯Ø©. ÙŠÙ‡Ø¯Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ÙˆØµÙ Ù…Ø´ÙƒÙ„Ø§Øª ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„ØÙ„ÙˆÙ„ Ø§Ù„ØªÙŠ ÙŠØ·Ø¨Ù‚Ù‡Ø§ Ø§Ù„Ù…Ø¹Ù„Ù…. Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ø¨ØØ« Ø§Ù„Ù†ÙˆØ¹ÙŠ. Ø·Ø±ÙŠÙ‚Ø© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù‚Ø§Ø¨Ù„Ø©. Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù‡ÙŠ Ù†Ø·Ù‚ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ‚Ù„Ø© Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª. ÙˆØ§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ØºÙŠØ± Ø§Ù„Ù„ØºÙˆÙŠØ© Ù‡ÙŠ Ø¨ÙˆØ§Ø³Ø·Ø© Ø§Ù„ØªØ¹Ù„Ù… ØºÙŠØ± ÙƒØ§ÙÙŠØ© ÙˆÙˆÙ‚Øª Ø§Ù„Ø¯Ø±Ø³ Ù„ÙŠØ³ ÙƒØ§ÙÙŠØ§. ØÙ„ÙˆÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ù‡ÙŠ ØªØ·Ø¨ÙŠÙ‚ Ø·Ø±Ù‚ ØªÙƒØ±Ø§Ø± Ù†Ø·Ù‚ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ØÙØ¸ Ø®Ù…Ø³ Ù…ÙØ±Ø¯Ø§Øª ÙƒÙ„ Ø§Ù„Ù„Ù‚Ø§Ø¡ØŒ ÙˆØ§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ù…ÙˆØ¬ÙˆØ¯Ø© ÙˆØªØ·Ø¨ÙŠÙ‚ Ø·Ø±Ù‚ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø©ØŒ ÙˆØªÙ†ÙÙŠØ° Ø§Ù„ÙŠÙˆÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠ. ÙŠÙ„Ø²Ù… Ù…Ø¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù‚Ø§Ø¯Ø± Ø¹Ù„Ù‰ ØÙ„ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª.